Proceedings of the 5th Conference on Information Technology Education 2004
DOI: 10.1145/1029533.1029568
|View full text |Cite
|
Sign up to set email alerts
|

An implementation of a networking track in an information technology degree program

Abstract: This paper will layout the University of Cincinnati's efforts in creating a networking track specialization for an information technology (IT) degree program to be started in the autumn quarter of 2004. The work done creating such an academic specialization for students is based on ACM SIGITE's initial implementation of IT curriculum guidelines. Input for the IT networking specialty was also obtained from faculty, students, and industry partners. Processes by which specific course offerings were chosen will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Curriculum development described in Stockman et al (2004) involves obtaining input from faculty members, students, and industry partners. Some of the lessons were learned the hard way after, "students voiced to faculty that they did not want to be software developers, but instead were more interested in networking" (p. 140).…”
Section: Theoretical Background: Experiences From Elsewherementioning
confidence: 99%
“…Curriculum development described in Stockman et al (2004) involves obtaining input from faculty members, students, and industry partners. Some of the lessons were learned the hard way after, "students voiced to faculty that they did not want to be software developers, but instead were more interested in networking" (p. 140).…”
Section: Theoretical Background: Experiences From Elsewherementioning
confidence: 99%
“…In some cases individuals were specifically approached to advise on curriculum and to be part of the advisory committee for the department. Industry sources were researched along with the current information technology research (Dark, Ekstrom, & Lunt, 2005;Hazem et al, 2004;Kamali, Liles, Winer, Jiang, & Nicolai, 2005;Stockman, Chaytor, et al, 2004;Stockman, Christopherson, et al, 2004) in an effort to holistically address the issues of student employment or graduate school acceptance upon gradua-tion. Partnerships continue to be sought in an effort to expose students to a variety of opportunities and challenges within their field of specialization.…”
Section: • Site Certifiersmentioning
confidence: 99%
“…Outcome based objectives are an integral part of the ABET (Accreditation Board for Engineering and Technology) accreditation guidelines. The literature supporting information technology education (Aasheim, Lee, & Reichgelt, 2005;Dark, Ekstrom, & Lunt, 2005;Hazem et al, 2004;Said et al, 2004;Stockman, Chaytor, et al, 2004;Stockman, Christopherson, Said, & Nyland, 2004) and supporting using outcome based objectives (Abernethy, Treu, Piegari, & Reichgelt, 2005;Longenecker Jr. & Feinstein, 2005 ) to define the graduating student, then the specific requisite knowledge, skills, and abilities (KSA's) of the student's primary focus area. A graduate of the program should have specific sets of KSA's spread across the curricula.…”
Section: Introductionmentioning
confidence: 99%
“…The courses required for the networking track as primary are 30 credit hours adding only senior design and the special topics. [10] Students can complete two primary tracks using this opportunity.…”
Section: Integrating Secondary and Elective Modulesmentioning
confidence: 99%
“…However, it was found that it does not matter which three classes, students take to fulfill the secondary requirement as long as the pre-requisites are satisfied. Details of the courses required for these tracks are available in the curriculum of the IT program at CAS [1] and in Said et al [7] and Stockman et al [10].…”
Section: Details Of the Secondary Specialtiesmentioning
confidence: 99%